Katecheza moralna o roztropności w De officiis ministrorum św. Ambrożego - Zając, Marian (Vox Patrum, 2008)
In the times when fewer and fewer Christians grant the Church the right to interpret the Gospel in a manner obligatory for them, it is worth mentioning the science of great teachers of the Church who were capable of awakening the Evangelical enthusiasm in their listeners. It seems that St Ambrose from Milan’s proposals excellently correspond with the spiritual way of catechesis renewal proposed at the beginning of the 20“ century by Pope Benedict XVI. It consists in prudently facing a human being with high moral demands in order to build the community of faith. In his moral catechesis conceming the virtue of prudence, St Ambrose enumerated the principles of effective catechesis aimed at a secularized human being. Rediscovery of such inspirations may lead to an increase in the attractiveness of current catechetical message and in its Evangelical potential.